Moral distress in nursing students: Recognizing and addressing an overlooked challenge - Conte, Luana; Lupo, Roberto; Cascio, Donato; Artioli, Giovanna; Caldararo, Cosimo; Antonazzo, Marcello; Petrelli, Cosimo; Greco, Federico; Lezzi, Alessia; Zacchino, Simone; Vitale, Elsa; De Nunzio, Giorgio (Acta Biomedica Atenei Parmensis, 2025)
Introduction: For nursing professionals, making decisions and taking actions in the face of illness can pose a new challenge each time, even though it is an expression of their professional role. At times, some decisions may go against customary practices, organizational policies, or institutional healthcare policies, causing moral distress. This phenomenon of moral distress also affects the population of nursing students, and it represents a critical threshold that should not be underestimated. Materials and methods: We conducted an online survey among Italian nursing students using a snowball sampling approach. The survey was conducted from January 2023 to April 2023, and social media platforms such as Facebook, Instagram, and WhatsApp were used as communication channels. Results: A total of 350 nursing students enrolled in various nursing programs across Italy participated in the study. The majority of participants were female, aged between 19 and 42 years (average = 23.21). The study results revealed that students can experience moral distress, with a correlation between moral distress and nursing student clinical placements. There was a stronger association with the potential harm factor compared to the factor of futility, indicating that students were significantly affected by moral and ethical work conditions. Conclusions: The students who participated in the study showed that not only were they unaware of the concept of moral distress, but they experienced it unknowingly and on a daily basis during clinical practice. Given the widespread nature of this phenomenon, it is of paramount importance to promote educational strategies for nursing students from their first year of studies to help them cope with moral distress during their clinical training.